Sporothrix schenckii in a hospital and home environment in the city of Pelotas/RS - Brazil - Mattei,Antonella S. (2011)
This study describes the isolation of S. schenckii in hospital and home environments in Brazil. Samples were collected from surfaces of a veterinary service place and at home. S. schenckii was detected in 1.5% of the samples from the hospital environment. However, this fungus was isolated from all sampled areas in home environments. The isolation of S. schenckii deonstrates that these surfaces could act as infection sources to anials and huans. Therefore, employees and pet owners could be exposed to this agent, and the contamination, through surfaces, could occur through the traumatic inoculation of the fungus or by direct contact with pre-existing lesions.